2010
DOI: 10.3109/10582452.2010.483967
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Low-dose Mivacurium to Lidocaine for Intravenous Regional Anesthesia

Abstract: Objectives: The current study aimed to evaluate low dosage of mivacurium added to lidocaine for intravenous regional anesthesia [IVRA].Methods: The present study used a double-blind methodology. The study group comprised 60 patients with the American Society of Anesthesiologists physical status I and II, who were scheduled to undergo carpal tunnel release as an outpatient procedure. Patients were randomly divided into two groups. In the mivacurium group [Group M; N = 30], intravenous regional anesthesia was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Mizrak et al50 found similar results to the previous studies, demonstrating a faster onset of sensory block by adding mivacurium (0.6 mg) to plain lidocaine (3.1 ± 0.5 minutes vs 2.2 ± 0.8 minutes). No study identified a difference in sensory recovery compared to control 6,50…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…Mizrak et al50 found similar results to the previous studies, demonstrating a faster onset of sensory block by adding mivacurium (0.6 mg) to plain lidocaine (3.1 ± 0.5 minutes vs 2.2 ± 0.8 minutes). No study identified a difference in sensory recovery compared to control 6,50…”
Section: Resultssupporting
confidence: 74%
“…The muscle relaxants investigated were pancuronium,33,38,44 atracurium,49,51,52 mivacurium,41,50,53 and cisatracurium 6…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations